NASA’s astrophysics cross-observatory science support (ACROSS) initiative: enabling time-domain and multimessenger astrophysics - Humensky, T. B.; Roberts, C. J.; Barclay, T.; Caputo, R.; Cenko, S. B.; Civano, F.; Derleth, J.; Hedges, C.; Hui, M. C.; Kennea, J. A.; Kocevski, D.; Racusin, J.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The Astro2020 Decadal Survey recommended an investment in Time-Domain and Multimessenger Astrophysics (TDAMM) as the top-priority sustaining activity in space for the coming decade. One aspect of NASA’s response to this recommendation is a pilot project, the Astrophysics Cross-Observatory Science Support (ACROSS) initiative, designed to provide support to both missions and observers as they pursue TDAMM science. Here, we present our observations of needs in the community and initial plans for ACROSS activities, including services to facilitate and improve cross-mission follow-up planning and execution; a multimessenger web portal with links to existing mission resources, community tools, and information targeted for TDAMM general observers; development of “Smart target-of-opportunity submission page” proof-of-concepts; and ongoing development of a potential TDAMM general observing competitive grant solicitation. As the ACROSS pilot phase begins, we invite discussion of our plans with both missions and observers to better understand their needs and concerns.